Mathematical Model Analysis of Cervical Cancer Disease with Immunotheraphy - St. Budi Waluya; Eliya Ijtihadiyatun Fisabila (Unnes Journal of Mathematics, 2025)
Cervical cancer is one type of disease that has the highest risk of death in the female population in Indonesia. Almost 95% of cervical cancer in women is caused by Human Papillomavirus (HPV) infection, which is common in women of reproductive age. In this study, a mathematical model is discussed for the case of the spread of the HPV virus to become pre-cancerous with immunotheraphy treatment. This research was conducted by building a mathematical model, analyzing the equilibrium point, and interpreting the mathematical model with numerical simulations using Maple software. This study divides the population into 5 sub-populations including susceptible (S), infected (I), precancer (P), and treatment (T) sub-populations. From the model formed, the disease-free equilibrium point and endemic equilibrium point are obtained as well as the basic reproduction number . The disease-free equilibrium point is locally asymptotically stable when  and the endemic equilibrium point is locally asymptotically stable when . Based on the results of numerical simulation analysis, it is obtained that the immunotheraphy treatment  is greatly affects on individual recovery.